MODEL INTERNALISASI NILAI-NILAI KEAGAMAAN DI MA’HAD SUNAN AMPEL AL-ALI UIN MALANG - Triyo Supriyatno (lp2m-uin malang, 2006)
The principles of Religions values internalization found in the study are: (1) Faithful to Allah swt. Among santri (students) for the mercy in able to generate self confident, braveness, discipline, strong will to hard working and optimism; (2) Dzikrullah in able to improve braveness, self confident, discipline, and independence; (3) New challenger and hard duties during learning process can develop braveness, self confident, creativity, and independence; (4) Thust in all element, of Ma’had such as kyai-santri, ustadz-santri, and musyrif-santri and among santri can develop braveness, creativity, strong will to hard working and independence; (5) Learning process stressing on jama’ah can develop the will to study from the surroundings at any time and is intended to develop discipline, strong will to hardworking, creativity, self confident and positive thingking; (6) Jama’ah activities can develop self confident and the will to serve others; (7) Motivating action through love and doing kindness in jama’ah can develop discipline, hardworking, and independence; (8) Clear religious values in vision are descrited in personality profile and self image, positive perception to vision and high commitment to achieve cand develop religious values; (9) Management factor especially open management can develop the capability of self management, respontibility, discipline, self introspection, creativity, braveness, and optimism.